(untitled) (Configurazioni. Research on contemporary poetry, 2022)
The aim of this contribution is to investigate the role of poetry in Elsa Morante’s production, focusing specifically on the author’s second poetic experiment Il mondo salvato dai ragazzini, published in 1968. Alongside the analysis of the main formal characteristics of an extremely heterogeneous work, the intention is to reflect on the meanings that the choice of the poetic word conveys for an author traditionally better known for writing in prose. The article also aims to consider the relationships this book establishes with its literary or philosophical models and its place in the contemporary socio-cultural scenario.